2022
DOI: 10.3389/fsurg.2022.844475
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Home Enteral Nutritional Support Compared With Normal Oral Diet in Postoperative Subjects With Upper Gastrointestinal Cancer Resection: A Meta-Analysis

Abstract: IntroductionWe performed a meta-analysis to evaluate the influence of a home enteral nutritional support compared with a normal oral diet in postoperative subjects with upper gastrointestinal cancer resection.MethodsA systematic literature search up to December 2021 was done and 23 studies included 3,010 subjects with upper gastrointestinal cancer resection at the start of the study; 1,556 of them were given home enteral nutritional support and 1,454 were normal oral diet. We calculated the odds ratio (OR) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…In a meta-analysis of postoperative patients diagnosed with upper gastrointestinal cancer, researchers concluded that home enteral nutritional support resulted in a significantly higher quality of life, better body weight change, and higher albumin and pre-albumin levels compared to an oral diet. 37 In another study on cachexia and pancreatic cancer, investigators concluded that enteral nutrition support positively affects weight gain. 38 Our study initiated ONS in 52.2% of the patients in the program, of whom 97% had been moderately or severely malnourished at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of postoperative patients diagnosed with upper gastrointestinal cancer, researchers concluded that home enteral nutritional support resulted in a significantly higher quality of life, better body weight change, and higher albumin and pre-albumin levels compared to an oral diet. 37 In another study on cachexia and pancreatic cancer, investigators concluded that enteral nutrition support positively affects weight gain. 38 Our study initiated ONS in 52.2% of the patients in the program, of whom 97% had been moderately or severely malnourished at baseline.…”
Section: Discussionmentioning
confidence: 99%